Development of Digital Calorimeter Experiment Kit to Train the Designing Experiments Ability of Pre-Service Science Teacher - Listiaji, Prasetyo; Dewi, Novi Ratna; Amalia, Andin Vita; Amelia, Rizki Nor; Widianingrum, Risti Ayu; Ardhani, Nadia Eka; Rahman, Nor Farahwahidah Abdul (STKIP Singkawang, 2024)
This study aims to develop a digital calorimeter experimental kit that is valid, accurate, precise, and as well and to analyze the profile of the ability to design experiments in pre-service science teachers after taking lectures using the digital calorimeter experiment kit. This research used the ADDIE model. The digital calorimeter that has been developed has digital innovation by using a digital temperature controller W1209 and an integrated heater. Expert validation results show valid criteria. The experimental results show a precision level of 98.9% and an accuracy rate of 95.6%. After the digital calorimeter was applied to lectures, a profile of the ability to design experimental science teacher candidates was obtained in the high category with an average score of 83.16. So it can be concluded that the digital calorimeter experimental kit developed is valid, accurate, precise, and able to train the ability to design experimental pre-service science teacher. The development of a digital calorimeter experiment kit can be an alternative to providing technology-based experiment tools and can also train the abilities of pre-service science teachers related to science experiments.